Water for food in Bangladesh: outlook to 2030 - Amarasinghe, Upali A.; Sharma, Bharat R.; Muthuwatta, Lal P.; Khan, Z.H. (International Water Management Institute, 2014)
This research study shows that ‘business-as-usual’ scenarios will have substantial production surpluses of rice, which dominates water use patterns in the country at present. However, the surpluses come at a considerable environmental cost, due to high levels of groundwater depletion. Bangladesh can mitigate potential groundwater crises by limiting rice production to meet the requirements of self-sufficiency. Increases in water productivity of both Aman (wet season) and Boro (dry season) rice production can help too. A carefully designed deficit irrigation regime for Boro rice can also increase transpiration, yield, water productivity and production, and reduce the pressure on scarce groundwater resources.